Quantum dot-sensitized solar cells having 3D-TiO(2) flower-like structures on the surface of titania nanorods with CuS counter electrode - Buatong, Nattha (Nanoscale Res Lett, 2015)
The photovoltaic performance of a quantum dot (QD)-sensitized solar cell consisting of CdS/CdSe/ZnS QDs loaded onto the surface of the three-dimensional (3D) flower-like TiO(2) structure grown on an array (1D) of TiO(2) nanorods (FTiR) is studied. The flower-like structure on the rod-shaped titania was synthesized using a double-step hydrothermal process. The FTiR array exhibited a 3D/1D composite structure with a specific surface area of 81.87 m(2)/g. Using CuS as the counter electrode instead of Pt offers the best performance and leads to an increase in the conversion efficiency (η). The efficiency of the CdS/CdSe/ZnS QD-loaded FTiR assembling CuS counter electrode cell improved from η = 2.715% (Voc = 0.692 V, Jsc = 5.896 mA/cm(2), FF = 0.665) to η = 0.703% (Voc = 0.665 V, Jsc = 2.108 mA/cm(2), FF = 0.501) for the QD-loaded FTiR assembling Pt counter electrode cell. These studies reveal a synergistically beneficial effect on the solar-to-current conversion of these QD-sensitized solar cells when a CuS counter electrode is used instead of the usual Pt counter electrode.